Courts and terrorism nine nations balance rights and security - Volcansek, Mary L. 1948-; Stack, Jr, John F.; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2010)
"Since ancient times, terror tactics have been used to achieve political ends and likely will continue into the foreseeable future. Preserving national security and the safety of civilian populations while maintaining democratic principles and respecting human rights requires a delicate balancing act. In democracies, monitoring that balance typically falls to the courts. Courts and Terrorism examines how judiciaries in nine separate nations have responded, not just to the current wave of Al Qaeda threats, but also to nacro-trafficking, domestic terrorism, and organized crime syndicates. Terrorism is not a new phenomenon, and even though the reactions have varied significantly, common themes emerge. This volume discusses eleven case studies and analyzes the experiences of these various nations in their battles with terrorism to reveal the judicial quandary for democratic governance and the rule of law in the twenty-first century" -- Provided by publisher
Introduction / Mary L. Volcansek -- Detention and security versus liberty in times of national emergency / David M. O'Brien -- One more casualty of the "war on terror" Aya Gruber -- State secrets and democratic values / Louis Fisher -- What lessons can be drawn from a sui generis case? The global "war on terror" and Northern Ireland / Richard Finnegan -- The British experience with terrorism : from the IRA to Al Qaeda / Mary L. Volcansek -- Detention and treatment of suspected terrorists under the European convention on human rights / Donald W. Jackson -- Australia's commonwealth model and terrorism / Michael C. Tolley -- Judicial rejection as substantial relief : the Israeli Supreme Court and the "war on terror" / Menachem Hofnung and Karen Weinshall-Margel -- Preserving rights and protecting the public : the Italian experience / Carlo Guarnieri -- Squaring the circle? : fighting terror while consolidating democracy in Spain / Blanca Rodriguez Ruiz -- From exception to normalcy : law, the judiciary, civil rights, and terrorism in Colombia, 1984-2004 / Victor M. Uribe-Urán and Harry Mora -- Conclusion : lessons learned / Mary L. Volcansek and John F. Stack, Jr.
Title from title screen (viewed on November 13, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Terrorism; Organized crime; National security -- Law and legislation; Courts; Criminal procedure